2023
DOI: 10.1021/acs.inorgchem.3c01042
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Chemical Bond between Lanthanides and Carbon: CeC, PrC, NdC, LuC, and TmC2

Abstract: Resonant two-photon ionization experiments have been conducted to probe the bond dissociation energy (BDE) of the lanthanide–carbon bond, allowing the BDEs of CeC, PrC, NdC, LuC, and Tm–C2 to be measured to high precision. Values of D 0(CeC) = 4.893(3) eV, D 0(PrC) = 4.052(3) eV, D 0(NdC) = 3.596(3) eV, D 0(LuC) = 3.685(4) eV, and D 0(Tm–C2) = 4.797(6) eV are obtained. Additionally, the adiabatic ionization energy of LuC was measured, giving IE­(LuC) = 7.05(3) eV. The electronic structure of these species, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 104 publications
0
15
0
Order By: Relevance
“…The photoionization spectrum of 24 Mg 132 Xe in the vicinity of the X + 2 Σ + (v + ) ← a 3 Π 0 (v″ = 0) ionizing transition of MgXe is compared with the PFI-ZEKE-PE spectrum of a natural sample of MgXe in Figure 2. The photoionization spectrum exhibits a sharp onset at the position corresponding to the adiabatic ionization energy of the a 3 Π 0 metastable state of 24 Mg 132 Xe [E I (v + = 0)/(hc) = 37,468.3(6) cm −1 , see below]. After a strong autoionization resonance at the position of the v + = 0 ionization threshold, the ion signal decreases.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The photoionization spectrum of 24 Mg 132 Xe in the vicinity of the X + 2 Σ + (v + ) ← a 3 Π 0 (v″ = 0) ionizing transition of MgXe is compared with the PFI-ZEKE-PE spectrum of a natural sample of MgXe in Figure 2. The photoionization spectrum exhibits a sharp onset at the position corresponding to the adiabatic ionization energy of the a 3 Π 0 metastable state of 24 Mg 132 Xe [E I (v + = 0)/(hc) = 37,468.3(6) cm −1 , see below]. After a strong autoionization resonance at the position of the v + = 0 ionization threshold, the ion signal decreases.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…The rotational constant for the a 3 Π 0 +/− state was taken from ref 3 as well as the 3 Π 0 + / 3 Π 0 − splitting of 1.46 cm −1 (the 0 − component lies below the 0 + one 3 ). The rotational constants of the X + state of 24 Mg 132 Xe + were obtained from the potential-energy function derived in this work (see Section 3.1.2). The vibrational and rotational constants of the other isotopomers were calculated using the appropriate mass-scaling laws.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Since the isolation of the first π- and σ-bonded organometallic lanthanides in 1954 by Wilkinson and Birmingham, and in 1972 by Cotton et al, respectively, organolanthanides have found synthetic and catalytic relevance in methanol synthesis, polymerization, olefin hydrogenation, hydrosilylation, alkyne dimerization, and even metallobiochemistry. The Ln–C bond has also become a focus of gas-phase studies, including laser-ablated lanthanide complexes probed via two-photon ionization or infrared spectroscopy. Unsurprisingly, then, there are many reviews detailing aspects of organolanthanide bonding, spanning oxidation states II, III, and IV (Roman numerals implying formal oxidation states), as well as σ- and π-bonds. , Organolanthanides are categorically sensitive to air and moisture and involve electrostatic Ln–C bonds exhibiting fast ligand exchange (e.g., exchanging alkyls or cyclopentadienyl with halides in FeCl 3 and UCl 4 to form the more covalent Fe–C and U–C analogues or scrambling bridging and terminal alkyls intramolecularly). Thus, organolanthanides require steric bulk and coordinative saturation to stabilize molecular complexes.…”
Section: Introductionmentioning
confidence: 99%